30-Min Exposure to Tobacco Smoke Influences Airway Ion Transport—An In Vitro Study. - Henke, Katarzyna; Balcerzak, Irena; Czepil, Ewa; Bem, Alicja; Piskorska, Elżbieta; Olszewska-Słonina, Dorota; Woźniak, Alina; Szewczyk-Golec, Karolina; Hołyńska-Iwan, Iga (Current Oncology, 2023)
Introduction: Smoking is one of the most important causes of cancer in humans. However, it has not been proven how long exposure to cigarette smoke is sufficient to induce cancerogenesis. Cigarette smoke can cause changes in ion and water transport and the maintenance of mucociliary transport. The conducted research concerned the assessment of changes in ion transport in rabbit tracheal specimens after 30 min of exposure to cigarette smoke. Materials and Methods: A modified Ussing chamber was used to measure the transepithelial electrical potential under stationary conditions (PD) and during mechanical stimulation (PDmin), and the transepithelial electrical resistance (R) in control and cigarette smoke-exposed tracheal fragments. Results: Significant changes in PD (−2.53 vs. −3.92 mV) and PDmin (−2.74 vs. −0.39 mV) were noted for the samples exposed to smoke, which can be associated with a rise in reactivity after applying a mechanical stimulus. In addition, the measured R (108 vs. 136 Ω/cm2) indicated no changes in the vitality of the samples, but an increase in their permeability to ions in the experimental conditions. Conclusions: A single 30-min exposure to cigarette smoke has been shown to be associated with increased permeability of the tracheal epithelium to ions and thus to substances emitted during smoking, which might be sufficient to create the possibility of initiating procarcinogenic processes.